Colonial Governance and Territorial Control In The Fergana Valley: The Formation Of The Fergana Oblast Administration - Raupova Mushtariybegim (International Journal Of History And Political Sciences, 2025)
This article examines how the Russian Empire institutionalized colonial rule in the Fergana Valley through the creation of the Fergana Oblast (province) administration after the liquidation of the Kokand Khanate. Focusing on the formative period from 1876 through the first decade of consolidated imperial governance, the study interprets “territorial control” as a complex assemblage of legal classification, spatial re-organization, bureaucratic staffing, fiscal extraction, and mediated authority. The establishment of the oblast did not merely extend an existing administrative template; it translated military conquest into an operational regime of rule by producing new borders, re-scaling local communities into imperial units, and formalizing a hierarchy of offices that connected Turkestan’s Governor-General to district and rural levels. Special attention is paid to the early uezd (district) structure, the relocation and symbolic “re-foundation” of the administrative center, and the use of statistical reporting as a governing technology. The article argues that the Fergana oblast administration became effective not primarily through the immediate replacement of local institutions, but through selective incorporation of indigenous intermediaries and normative pluralism, while retaining coercive capacity as a background condition. At the same time, the administrative order remained structurally constrained by limited personnel, informational asymmetries, and persistent contestation over land, water, and jurisdiction. The Fergana case demonstrates how imperial territorialization in Central Asia fused military, civil, and epistemic tools into a distinctive late-imperial colonial governance model.